Positive Youth Development Program, Stimulator to Increase Competences For Sexual Educator: A Documentation Study - Andhika Alexander Repi (Universitas Katolik Widya Mandala Surabaya, 2017)
Sexual harassment; teenager premarital sexual activities; and sexually transmitted infections (STIs) among teenager are remain alarmingly high for Indonesian youth. Actually, these three phenomena can be overcome by conduct sex education training. Researchers found that sex education training is still an effective way to prevent youth from those phenomenons and enhance the well being of them. The ideal sex educators are parents and teacher as a closest side to the youth. But, In Indonesia, sex educator still threat by many constraints such as belief of discussion about sex is taboo, lack of knowledge, and lack of confidence to conduct the training.This gap could overcome by developing program called Positive Youth Development Program. Design of this program consist of two topic, the sex education training for the youth, and training of trainer for the sex educator. This paper focused on how to preparing sex educators in case of conduct the Positive Youth Development Program. The discussion on this paper come out with two topics: (1) What is Positive Youth Development Program: concept and training topic and (2) how to be a good sex educator: how to design the program, and how to deliver the positive youth development program.